Coursing paths: 15th anniversary of Rev Rene - Cardoso, Maria Vera Lúcia Moreira Leitão (Rev Rene, 2015)
To contemplate aspects of a journal which experiences what we call “adolescence process” isindeed challenging. We have traveled paths, sometimes easy, sometimes difficult, in which we advocatethat if a seed is thrown into fruitful soil, the results certainly will present as productive. This isthe case of Rev Rene. To become adolescent is being in the world. It is creating complicity to dream